2020
DOI: 10.2174/1573404817666201221121247
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Personality Types and Sexual Dysfunction

Abstract: Background: Sexual function is affected by various physiological and psychological factors. Individual differences and various personality types are effective in response to sexual function. Objective: The present study aimed to investigate the correlation between sexual function and personality types among the women referred to healthcare centers in Shiraz in 2014-2015. Methods: This cross-sectional, descriptive-analytical study was conducted on 514 women referred to healthcare centers in Shiraz. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Facing various pressures caused by infertility, these people are more likely to produce and accumulate negative emotions such as anxiety and depression (Maroufizadeh et al, 2015). The present study indicated that neurotic personality may influence the normal process in the sexual function of men, which is consistent with the research that sexual dysfunction is accompanied with a higher score of neuroticism (Hosseini et al, 2021). We speculated that the psychological distress may mediate the association between neuroticism and sexual dysfunction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Facing various pressures caused by infertility, these people are more likely to produce and accumulate negative emotions such as anxiety and depression (Maroufizadeh et al, 2015). The present study indicated that neurotic personality may influence the normal process in the sexual function of men, which is consistent with the research that sexual dysfunction is accompanied with a higher score of neuroticism (Hosseini et al, 2021). We speculated that the psychological distress may mediate the association between neuroticism and sexual dysfunction.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, neurotic personality also has a predictive effect on TEF occurrence (Hosseini et al, 2021). Neurotic people are prone to illogical thinking, poor impulse control, and poor stress management, consistent with the previous studies, people with neurotic personalities have higher levels of psychological distress and are more likely to suffer from common mental illnesses (Jeronimus et al, 2014(Jeronimus et al, , 2016.…”
Section: Discussionsupporting
confidence: 83%